Small fashion business owners and their businesses in the Vaal region - Van Wyk, Arrie Willem (My University, 2013)
Introduction: Entrepreneurial fashion businesses are very important due to the employment, income, products and services they provide. The South African government has identified small, medium and micro enterprises (SMMEs) to address the economic challenges in this country. Entrepreneurship development is a means to economic development, which implies developing an entrepreneurial population. Aim: To acquire an integrated perspective on fashion entrepreneurs, their businesses and the technological environment in which they function, in order to understand the maintaining of a successful fashion business and to offer recommendations for the training and development of potential and existing fashion entrepreneurs. Method: A convenience sample of 100 fashion entrepreneurs in the Vaal Region was selected. A self-administered, structured questionnaire was compiled and used to gather the information. Section A focused on demographic background information, section B investigated entrepreneurial attributes, section C investigated the start-up and functioning of the business and section D concentrated on the technological environment. The instrument was tested for validity and reliability. Results: There were more female than male respondents, which corresponds with recent global statistics. The age distribution of these fashion entrepreneurs was quite balanced between younger, middle and older groups. Nearly three-quarters of the respondents were married, mostly with children aged older than 19 years. The majority of these fashion entrepreneurs had a tertiary qualification, but only a fifth had formal business training while negligibly few had formal training in business management or other business training. Six desirable entrepreneurial attributes were investigated and ranked in the following order: Leadership; Commitment and determination; Motivation to excel; Creativity, self-reliance and ability to adapt; Customer service; Tolerance of risk, ambiguity and uncertainty. All the attributes except the last one were scored quite high. They possessed most required entrepreneurial skills and knowledge, but lacked training in specific areas. Most ran their businesses as a sole career, employing one to four people and relied on the word-of-mouth advertising method. They used computers and information technology to a moderate extent and industrial equipment to a low extent.
Keywords: 391.096822; Clothing trade -- South Africa; Retail trade -- South Africa; Fashion merchandising -- South Africa